A fruitful contact with the ‘Lifestyle’ and ‘Arts and Entertainment’ pages of The Daily Star - Sohana, Shahi (BRAC University, 2016)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015.